How are motor skills and writing readiness in children? A literature review - Antonius Totok Priyadi; Isti Dwi Puspita Wati; Amriani Amir; Tulus Gover Siringo-ringo; Yohanes Gatot Sutapa Yuliana; Fifukha Dwi Khory; Putra Sasataman B; Dyoty Auliya Vilda Ghasya; Procopio B. Dafun JR; Mimi Haetemi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Writing is one of the basic skills for moving up in the world of education and eventually carries over into adult life to interact in both communication and work. Basically, learning to write is a complex process that is integrated with the child's memory experience, combining meaningful visual and motor stimuli that are captured on paper. The study of writing is interesting from a motor perspective. This literature review research aims to examine writing from a motor perspective. Review articles were searched on Scopus and PubMed search engines with the keywords "writing AND motor AND skills". Initially 1,171 documents were found on Scopus and 1,059 on PubMed. After restriction based on year, theme, age specific, relevant abstract and full article reading, 10 articles met the criteria. The conclusion of this review explains that writing is a fine motor skill, especially visual motor. In fact, this skill does not automatically mature without the contribution of growth (physical), maturity (quality), intervention (learning and experience), and treatment (learning process).